The Soviet Occupation of Afghanistan: Implications for Muslim Central Asia and the Muslim World (American Journal of Islam and Society, 1986)
ISLAM is as natural to the people of Afghanistan as the air they breathe.Any system repugnant to Islam or the introduction of alien forces to introducea new social order has always been resisted by the Afghans. The presentAfghan-Soviet war is one such story.The war is a matter of vital importance because its outcome will immenselyaffect Pakistan, Iran, and the rest of the Muslim world. It will also upset thebalance of power between the West and the Soviets, and might change thedirection of oil flow. It is curious that the war is not given the support orattention it deserves, in spite of its global ramifications. The West perhapsignores the war as Afghanistan is far removed from the Western mainstream,and its impact is not generally understood because the Afghan Mujahideenlack a sophisticated network of information. Moreover, the Soviets continuemisleading the world by claiming the war is only a law and order problembetween the Afghan government and a handful of “bandits” encouraged fromoutside.The war is neither a law and order matter nor its impact hard to realize.Afghan Mujahideen are fighting the Soviets to force them out of Afghanistan,and the Soviets are trying to hold on using biological, chemical, and othersophisticated weapons. In spite of enormous destruction and genocide, theAfghan Mujahideen are determined to fight to the last, and so apparently arethe Soviets to consolidate their occupation of Afghanistan. This paper presentsan analysis of the war and its impact on Pakistan, the Muslim world, andthe West from a geopolitical standpoint. A brief discussion of Afghanistanexplains the former status of Afghanistan as a buffer state first between theRussians and the British and later between the Soviets and Pakistan.Modern Afghanistan dates back to 1747 when Ahmad Shah Durrani tookover reins of that country. More or less during the same time, the British ...